For this case we have an expression of mixed numbers:
[tex]5 \frac {1} {2} = \frac {2 * 5 + 1} {2} = \frac {11} {2}\\4 \frac {1} {4} = \frac {4 * 4 + 1} {4} = \frac {17} {4}\\6 \frac {3} {4} = \frac {4 * 6 + 3} {4} = \frac {27} {4}[/tex]
Rewriting the expression we have:
[tex]- \frac {11} {2} - \frac {17} {4} -\frac {27} {4} =[/tex]
Remember that equal signs are added and the same sign is placed.
[tex]- \frac {11} {2} - \frac {44} {4} =\\- \frac {11} {2} - \frac {22} {2} =\\- \frac {33} {2}[/tex]
Answer:
[tex]- \frac {33} {2}\\-(15 \frac {3} {2})[/tex]